1991
DOI: 10.2105/ajph.81.6.762
|View full text |Cite
|
Sign up to set email alerts
|

The microbiologic quality of drinking water in North Carolina migrant labor camps.

Abstract: A two-year study of the microbiological quality of drinking water in 27 randomly selected North Carolina migrant labor camps yielded total and fecal coliform prevalences of 44 percent and 26 percent, respectively in 1988 and similar but higher prevalences in 1989. Preoccupancy testing by county sanitarians had found virtually no total coliform contamination. These findings suggest that a potential source of contamination existed and that current testing protocols which rely on preoccupancy testing may be inade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…In North Carolina, 9.5% of randomly selected residents of farm labor camps had parasitic infections (17). A companion study of drinking water in North Carolina labor camps found total and fecal coliform levels of 44% and 28%, respectively, but none had detectable levels in advance of occupancy (16). The authors suggest that water testing be conducted regularly during peak occupancy rather than just prior to the arrival of worker residents.…”
Section: The Control Of Infectious Diseasesmentioning
confidence: 96%
“…In North Carolina, 9.5% of randomly selected residents of farm labor camps had parasitic infections (17). A companion study of drinking water in North Carolina labor camps found total and fecal coliform levels of 44% and 28%, respectively, but none had detectable levels in advance of occupancy (16). The authors suggest that water testing be conducted regularly during peak occupancy rather than just prior to the arrival of worker residents.…”
Section: The Control Of Infectious Diseasesmentioning
confidence: 96%
“…For example, 44% of water supplies for migrant farm workers in North Carolina tested positive for coliform and 26% for fecal coliform. For comparable farm areas in the same 308 EVANS KANTROWITZ region, both levels were at 0% (23). Low-income Chicano populations living along the U.S./Mexico border (Colonias) are plagued by contaminated drinking water.…”
Section: Water Pollutionmentioning
confidence: 99%
“…At the same time, farmworkers are at substantially greater risk than the general population for exposure to occupational injuries, communicable diseases (e.g., tuberculosis and HIV/AIDS), and dental diseases. [18][19][20][21][22][23][24][25][26] There is great concern about occupational exposure of farmworkers to agricultural chemicals and the short-and long-term effects of this exposure. [27][28][29][30] Farmworkers in North Carolina are overwhelming minority-group members, composed almost exclusively of Hispanic and African American workers.…”
Section: Case Study: Enhancing the Participation Of North Carolina Famentioning
confidence: 99%